The unexpectedly short Holocene Humid Period in Northern Arabia - Neugebauer, Ina; Dinies, Michèle; Plessen, Birgit; Dräger, Nadine; Brauer, Achim; Brückner, Helmut; Frenzel, Peter; Gleixner, Gerd; Hoelzmann, Philipp; Krahn, Kim J.; Pint, Anna; Schwab, Valérie F.; et al. (Communications earth & environment, 2022)
The early to middle Holocene Humid Period led to a greening of today’s arid Saharo-Arabian desert belt. While this phase is well defined in North Africa and the Southern Arabian Peninsula, robust evidence from Northern Arabia is lacking. Here we fill this gap with unprecedented annually to sub-decadally resolved proxy data from Tayma, the only known varved lake sediments in Northern Arabia. Based on stable isotopes, micro-facies analyses and varve and radiocarbon dating, we distinguish five phases of lake development and show that the wet phase in Northern Arabia from 8800-7900 years BP is considerably shorter than the commonly defined Holocene Humid Period (~11,000-5500 years BP). Moreover, we find a two century-long peak humidity at times when a centennial-scale dry anomaly around 8200 years BP interrupted the Holocene Humid Period in adjacent regions. The short humid phase possibly favoured Neolithic migrations into Northern Arabia representing a strong human response to environmental changes.